2014
DOI: 10.1007/s11356-014-3121-3
|View full text |Cite
|
Sign up to set email alerts
|

Public budgets for energy RD&D and the effects on energy intensity and pollution levels

Abstract: This study, based on the N-shaped cubic model of the environmental Kuznets curve, analyzes the evolution of per capita greenhouse gas emissions (GHGpc) using not just economic growth but also public budgets dedicated to energy-oriented research development and demonstration (RD&D) and energy intensity. The empirical evidence, obtained from an econometric model of fixed effects for 28 OECD countries during 1994-2010, suggests that energy innovations help reduce GHGpc levels and mitigate the negative impact of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(57 citation statements)
references
References 39 publications
4
52
1
Order By: Relevance
“…Therefore, adequate environmental regulation could effectively accelerate technology changes capable of reducing pollution (Torras and Boyce, 1998). Many studies have demonstrated that changes in the energy-mix pattern and the promotion of renewable energy sources have a direct impact on reducing CO2 emissions (Balsalobre et al, 2015).…”
Section: Model Construction and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, adequate environmental regulation could effectively accelerate technology changes capable of reducing pollution (Torras and Boyce, 1998). Many studies have demonstrated that changes in the energy-mix pattern and the promotion of renewable energy sources have a direct impact on reducing CO2 emissions (Balsalobre et al, 2015).…”
Section: Model Construction and Datamentioning
confidence: 99%
“…In an N-shaped scheme, ENERG_INNOVit provides technical compensation for the scale effect ( Figure-3 (Torras and Boyce, 1998;Balsalobre et al, 2015). High-income countries that invest in energy innovation processes, use high-technology equipment, and operate in a more service-centred economy generate large differences in the trade preconditions of developed and developing countries.…”
Section: Figure-4 Inflection Pointmentioning
confidence: 99%
“…(2) and Eq. (3) that our study focuses on investigating whether the association between economic growth and carbon emissions is either an N-shaped or inverted N-shaped EKC (see Shafik and Bandyopadhyay, 1992;Grossman and Krueger, 1995;Torras and Boyce, 1998;Balsalobre et al, 2015;Sinha andBhattacharya, 2016, 2017; Álvarez-Herranz et al, 2017 a, b, and others) 5 . The N-shaped pattern allows us to focus on issues that are related to scale effect and the long-term effects of energy 4 Renewable energy consumption data does not include biomass energy consumption.…”
Section: In This Model Per Capita Gdp Is Presented In Current Us Dolmentioning
confidence: 99%
“…Following Lopez-Menendez et al (2014) and Balsalobre et al(2015), we categorize the patterns of the relationships using coefficient parameters , ,and estimated by equations (1) and (2). We summarize the patterns of the relationships in Table 3.…”
Section: -1 Definition Of the Ekc Relationshipmentioning
confidence: 99%